25 YEARS ON: THE LINGUISTIC SITUATION FROM THE REPUBLIC OF MOLDOVA - Inga DRUŢĂ (Academy of Sciences of Moldova, 2014)
The present contribution is revealing in terms of 25-year period covered in Moldova since 1989, from adoption of language laws, till today. Linguistic realities past and present are analyzed in terms of the identity crisis that grinds Moldovan society faces two fi elds antagonistic forces: on the one hand, the Soviet legacy, one that pulls in the past, on the other hand, the demands of modernization, adaptation to Western civilized world standards.